Molecular and phylogenetic identification of an oil-producing strain of Nannochloropsis oceanica (Eustigmatophyceae) isolated from the southwestern Atlantic coast (Argentina) - Bongiovani, Natalia Soledad (2014)
Screening of local microalgae species with potential for oil production is essential to achieve successful commercial large-scale cultures. In this study, identification of a South American species of Nannochloropsis was carried out using molecular and phylogenetic analyses of chloroplastic and nuclear genes, rcbL and 18S rDNA, respectively. The gene sequences for the studied strain were highly similar to other strains of Nannochloropsis oceanica (100% for 18S rDNA and 99.7% for rbcL) isolated from the Red Sea or Mediterranean Sea (Israel) and from the Pacific Ocean (Japan).